The Role of Molecule Clustering by Hydrogen Bond in Hydrous Ethanol on Laminar Burning Velocity - I Made Suarta; I. N. G. Wardana; Nurkholis Hamidi; Widya Wijayanti (Journal of Combustion)
The role of hydrogen bond molecule clustering in laminar burning velocities was observed. The water in hydrous ethanol can change the interaction between water-ethanol molecules. A certain amount of water can become oxygenated which increases the burning velocity. The hydrogen bond interaction pattern of ethanol and water molecules was modeled. Based on the molecular model, azeotropic behavior emerges from ethanol-water hydrogen bond, which is at a 95.1%v composition. The interaction with water molecule causes the ethanol molecule to be clustered with centered oxygenated compound. So, it supplies extra oxygen and provides intermolecular empty spaces that are easily infiltrated by the air. In the azeotropic composition, the molecular bond chain is the shortest, so hypothetically the burning velocity is anticipated to increase. The laminar burning velocity of ethanol fuel was tested in a cylindrical explosion bomb in lean, stoichiometric, and rich mixtures. The experimental result showed that the maximum burning velocity occurred at hydrous ethanol of 95.5%v composition. This discrepancy is the result of the addition of energy from 7.7% free ethanol molecules that are not clustered. At the rich mixture, the burning velocity of this composition is higher than that of anhydrous ethanol.